Peran Kualitas Pelayanan Dalam Meningkatkan Minat Wisatawan Menuju Destinasi Wisata Kawasan Pulau Mandeh, Sumatera Barat - Rahmayeni, Zulwida; Mulyana, Cahyana Agung; Syafran, Syafran; Emriadi, Haviz; Sari, Putri Puspita (Journal of Tourism Sciences, Technology and Industry, 2025)
This study aims to analyze the role of service quality in increasing tourists’ interest in visiting the Mandeh Island tourist destination, West Sumatra. A quantitative approach was applied through a survey of 50 purposively selected tourists. Service quality was measured using the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Tourist interest was assessed based on intentions to return, give recommendations, and engage in other tourism activities. The results show that all service quality dimensions were rated as good, with reliability scoring the highest (96%) and tangibles the lowest (86%). Tourist interest was also high, with intentions to return (90%), give recommendations (92%), and try other activities (80%). Regression analysis indicates that service quality has a significant influence on tourist interest. These findings highlight the importance of improving overall service quality to enhance the competitiveness and sustainability of the Mandeh Island tourist destination.